'Falling leaves return to their roots'? The reception of Chinese blockbusters by Chinese university students in New Zealand - Huffer I; Gong Y (Taylor and Francis Group, 2023)
This article examines the extent to which the films Wolf Warrior 2 (战狼2) (Wu 2017) and The Wandering Earth (流浪地球) (Guo 2019) might help to cultivate pride in the dream of a revitalised China among Chinese university students in New Zealand. A combination of state oversight, private capital and market forces have led to the People’s Republic of China’s (PRC) increased production of blockbuster films that promote the ‘Chinese Dream’. These films receive regular theatrical release within New Zealand but our understanding of how PRC university students in New Zealand respond to these films remains limited. Understanding this response is vital given the state’s view of these students as ‘civil ambassadors’ and ‘a diaspora in the making’. Using focus group data, the article shows how the reception of these films is complicated by the pluralised context of these films’ production and consumption, with the engagement of some participants pivoting upon issues of genre more than ethno-national identification. Nevertheless, for some of the participants these films do help to affirm their identities as Chinese and generate pride in a rejuvenated China via the complex ways in which these films connect to their lives.
Keywords: Chinese cinema; New Zealand Chinese film audiences; diasporic film audiences; Chinese dream; Chinese diaspora